A computational study of the HO2 + SO3 → HOSO2 + 3O2 reaction catalyzed by a water monomer, a water dimer and small clusters of sulfuric acid: kinetics and atmospheric implications. Issue 30 (22nd July 2022) - Zhang, Yongqi; Cheng, Yang; Zhang, Tianlei; Wang, Rui; Ji, Jianwei; Xia, Yu; Lily, Makroni; Wang, Zhuqing; Muthiah, Balaganesh
Abstract : The reaction mechanisms and kinetics for the HO2 + SO3 → HOSO2 + 3 O2 reaction catalyzed by a water monomer, a water dimer and small clusters of sulfuric acid have been studied theoretically by quantum chemical methods and the Master Equation/Rice–Ramsperger–Kassel–Marcus rate calculations. Abstract : Herein, the reaction mechanisms and kinetics for the HO2 + SO3 → HOSO2 + 3 O2 reaction catalyzed by a water monomer, a water dimer and small clusters of sulfuric acid have been studied theoretically by quantum chemical methods and the Master Equation/Rice–Ramsperger–Kassel–Marcus (ME/RRKM) rate calculations. The calculated results show that when H2 O is introduced into the HO2 + SO3 reaction, it not only enhances the stability of the reactant complexes by 9.0 kcal mol −1 but also reduces the energy of the transition state by 8.7 kcal mol −1 . As compared with H2 O, catalysts (H2 O)2, H2 SO4, H2 SO4 ⋯H2 O and (H2 SO4 )2 are more effective energetically, which not only results from a higher binding energy of 21.3–26.0 kcal mol −1 for the reactant complexes but also from a reduction of the energy of the transition states by 8.6–17.2 kcal mol −1 . Effective rate constant calculations show that, as compared with H2 O, catalysts (H2 O)2, H2 SO4, H2 SO4 ⋯H2 O and (H2 SO4 )2 can never become more efficient catalysts within the altitude range of 0–15 km due to their relatively lower concentrations. Besides, at 0 km altitude, the enhancement factor for the H2 O and ( k ′WD1 / k tot ) (H2 O)2 -assisted HO2 + SO3 reaction within the temperature range of 280–320 K was respectively calculated to be 0.31%–0.34% and 0.16%–0.27%, while the corresponding enhancement factor of H2 O and (H2 O)2 at higher altitudes of 5–15 km was respectively found only 0.002%–0.12% and 0.00001%–0.022%, indicating that the contributions of H2 O and (H2 O)2 are not apparent in the gas-phase reaction of HO2 with SO3 especially at higher altitude. Overall, the present work will give a new insight into how a water monomer, a water dimer and small clusters of sulfuric acid catalyze the HO2 + SO3 → HOSO2 + 3 O2 reaction.